### why does x + -8/9of x = 1/9 of x

Posted:

**Tue Dec 27, 2016 2:57 pm**Hi,

I accept that I'm atrocious at maths so please don't be too harsh

I'm trying to work my way through Bhaskara Lilavati where you work out the number of bees.

The equation is (the square root of x/2 )+ 8/9 of x + 2 = x

So I found an answer and the first 3 steps are as follows:

1.(square root of 1/2 of x) + 8/9 of x + 2 = x

2. add -2 to both sides

(square root of 1/2 of x )+ 8/9 of x + 2 + -2 = x + -2

(square root of 1/2 of x) + 8/9 of x = x -2

3. add -8/9 of x to both sides

(square root of 1/2 of x) + 8/9 of x + -8/9 of x = x - 2 + -8/9 of x

(square root of 1/2 of x) = 1/9 of x - 2?

My question is at step 3 how do you get from x - 2 + -8/9 of x to 1/9 of x - 2

If someone could explain this to me in real simple step by step terms I would be very grateful

I accept that I'm atrocious at maths so please don't be too harsh

I'm trying to work my way through Bhaskara Lilavati where you work out the number of bees.

The equation is (the square root of x/2 )+ 8/9 of x + 2 = x

So I found an answer and the first 3 steps are as follows:

1.(square root of 1/2 of x) + 8/9 of x + 2 = x

2. add -2 to both sides

(square root of 1/2 of x )+ 8/9 of x + 2 + -2 = x + -2

(square root of 1/2 of x) + 8/9 of x = x -2

3. add -8/9 of x to both sides

(square root of 1/2 of x) + 8/9 of x + -8/9 of x = x - 2 + -8/9 of x

(square root of 1/2 of x) = 1/9 of x - 2?

My question is at step 3 how do you get from x - 2 + -8/9 of x to 1/9 of x - 2

If someone could explain this to me in real simple step by step terms I would be very grateful